Prevention of burnout in nurses - Cielebąk, Sebastian; Dey, Beata; Hołubiuk, Hołubiuk; Sienkiewicz, Zofia; Imiela, Jacek (Nursing in the 21st Century, 2013)
PREVENTION OF BURNOUT IN NURSES Introduction. „Burnout” is a set of specific symptoms both mental and somatic that are a consequence of prolonged stress associated with a key and ongoing professional activity. Before burnout fully develops, symptoms that inform about the growing problems occur. An in-depth self-diagnosis allows undertaking precautionary measures and initiating changes in the desired direction. In order to prevent burnout syndrome it is necessary to: 1) emphasize the positive aspects of the practiced work and profession; 2) supplement the risk-awareness of burnout with countermeasures; 3) remember about professional development; 4) provide feedback and support; 5) get to know your goals, expectations, attitudes and feelings; 6) maintain your own autonomy; 7) treat professional issues less personally; 8) set yourself realistic goals; 9) take breaks from work, make sure to rest, relax and enjoy hobbies; 10) supplement the concern for others with concern for yourself. Aim. The goal of this thesis is the assessment of activities from the field of burnout prevention among nurses. Material and method. The research tool for this study was a self-prepared questionnaire composed of 15 test questions. The study was carried out from November 2011 until December 2012 among 700 nurses.